Assessment of tolerance to salt stress in Kenyan tomato germplasm - Agong', Stephen G.; Schittenhelm, Siegfried; Friedt, Wolfgang (International Journal of Plant Breeding, 1997)
Tomato is an important vegetable crop in Kenya and the development of salt tolerant cultivars would enhance its productivity in the vast marginal areas of the country. This study was aimed at determining the magnitude of genotypic variability for salt tolerance in the Kenyan tomato germplasm. Pot experiments with 22 landraces and 9 market cultivars were laid out as a two and four replicate split-plot design in glasshouse in Experiments 1 and 2, respectively. Salt treatments in Experiment 1 were 0 and 5 g NaCl kg-1 resulting into 0.5 and 9.1 dS m-1 of the soil saturation extracts, respectively. In Experiment 2 the treatments were 0, 4, and 8 g NaCl kg-1soil corresponding to 0.5, 7.4, and 14.2 dS m-1, respectively. Data were recorded on agronomic and biochemical parameters. The germplasm showed large variation for salt tolerance. Fruit and seed production at soil salinity of 14.2 dS m-1 demonstrated that these tomatoes are fairly tolerant of NaCl. Osmotic adjustment was achieved by higher fruit electrical conductivity, brix and total titratable acidity. Low and high contents of K+, Ca2+ and Mg2+ within tomato tissues and soil, respectively, under salt treatment, confirmed competition and antagonism involving Na+ and these cations. Low Na+ and Cl- contents in the fruit at 7.4 dS m-1 revealed their exclusion and ensured production of physiologically normal seeds and nutritionally healthy fruits. Two landraces ‘Chwerotonglo’ and ‘Nyanyandogo’ were identified as salt tolerant. Comparatively, the market cultivars showed superior fruit yields despite their susceptibility to salinity. Accordingly, tolerance of landraces in combination with superior yields of the market cultivars is suitable for tomato improvement for salt toleran
Keywords: Lycopersicon esculentum; tomato landraces; salt stress tolerance; osmotic adjustment; adaptation; breeding potential